Analisis Ekonomi dan Finansial Shortcut Tegineneng - Tarahan - Siagian, Andre Jonathan; Purba, Aleksander; Siregar, Amril Ma'ruf (Universitas Lampung, 2018)
Feasibility Analysis is an appropriate analysis of parameters to determine a successful implemented project or not. Feasibility analysis is divided into two parts economic and financial analysis that both affect the feasibility of a project. The purpose of this study is to determine the costs incurred in a railway shortcut project, to analyze delay times before and after a railway shortcut, and to find out which railway shortcut project meets the economic and financial feasibility requirements. In this study, an analysis of the economic and financial feasibility and summarize the economic viability benefits of the Tegineneng - Tarahan shortcut project was conduct. A project is declared feasible or not by doing comparison with the feasibility method that is NPV> 0, BCR> 1, PP faster than the specified time, IRR> capital cost, and PI> 1. This study uses full occupancy rate with discount rate of 5% , 10%, and 15%, respectively.Based on the results obtained in terms of economic feasibility analysis that investment evaluation does not qualify due to the amount of benefit is too small so that economic analysis is not feasible. The aspect of financial feasibility analysis and analysis by summing the two financial and economic benefits is eligible so that the Tegineneng - Tarahan shortcut project is categorized as feasible. Keyword : Economic Feasibility, Financial Feasibility, Feasibility Method